2015
DOI: 10.1155/2015/281870
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated Oral Mucosa Epithelium in Ocular Surface Reconstruction in Aniridia Patients

Abstract: Purpose. Efficacy of cultivated oral mucosa epithelial transplantation (COMET) procedure in corneal epithelium restoration of aniridia patients. Methods. Study subjects were aniridia patients (13 patients; 17 eyes) with irregular, vascular conjunctival pannus involving visual axis who underwent autologous transplantation of cultivated epithelium. For the procedure oral mucosa epithelial cells were obtained from buccal mucosa with further enzymatic treatment. Suspension of single cells was seeded on previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In oral and maxillofacial surgery, the main objective is the development of biocompatible oral mucosa equivalents as suitable graft materials. Extensive research is done on models for clinical applications such as burn treatment, 270 ocular surface reconstruction 271,272 or substitution urethroplasty. 273,274 Oral mucosa engineering in terms of advantages and disadvantages of different experimental set-ups, cell sources, scaffolds and applications for oral mucosa engineering has been extensively reviewed previously.…”
Section: Tissue-engingeering/organotypic Culturesmentioning
confidence: 99%
“…In oral and maxillofacial surgery, the main objective is the development of biocompatible oral mucosa equivalents as suitable graft materials. Extensive research is done on models for clinical applications such as burn treatment, 270 ocular surface reconstruction 271,272 or substitution urethroplasty. 273,274 Oral mucosa engineering in terms of advantages and disadvantages of different experimental set-ups, cell sources, scaffolds and applications for oral mucosa engineering has been extensively reviewed previously.…”
Section: Tissue-engingeering/organotypic Culturesmentioning
confidence: 99%
“…Over the past decades, several medical treatments for LSCD have been reported including amniotic membrane transplantation, autograft LSC and oral mucosa transplantation, allograft LSC and oral mucosa transplantation, and bone marrow derived mesenchymal stem cells (BMMSC) or epithelial stem cells derived from corneal epithelial cells. However, there is still no optimal treatment probably due to lack of knowledge of the underlying mechanisms during LSCD occurrence and recovery 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Stevens-Johnson syndrome had a more stable epithelium after CLET than patients with LSCD following burns or OCP. In one study which studied results of CLET in patients with aniridia, 3 out of the 13 female patients included had a lower rate of epithelium regularity (42). Ganger et al (29) followed the longterm outcomes in children and adults following CLET, however comparison between the two groups was not done due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, cultured sheets were not secured with sutures (13,14,35,37,43), however a therapeutic contact lens was used over the transplant. Nonetheless, a few authors reported suturing cultivated sheets to the conjunctiva (36,38,42). With patients also suffering from cataract, phacoemulsification and posterior chamber implant were performed simultaneously with COMET (40).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation